Hidden Environmental Vulnerability in Relation to the Instability of two Medieval Monastic Communities and Consequences for Present Environmental Management Options - Vingo, Paolo de; Vandewiele, Wim; Casazza, Marco; Lega, Massimiliano (Journal of Environmental Accounting and Management, 2026)
This paper aims at discussing the importance of environmental factors in the stability of communities at local scale. Two case studies, referred to two medieval monastic communities are chosen as historical examples, under low-carbon conditions, to show the effects of the interplay between a lack of Community Based Adaptation (CBA) and difficult or changing environmental conditions. The case studies refer to the monastery of Bobbio (Piacenza, Emilia-Romagna, Italy) and Castelletto Cervo (Biella, Piedmont, Italy). In particular, the first case shows a lack of transformation of harsh regulations to the difficult environmental conditions of that time, which leaded to a revolt inside the monastery. On the other side, the decline of Castelletto Cervo Cluniac priory depended upon a bad management of economic resources in a time of environmental variability, which affected the agricultural yield and the life of many villages in the considered area. The choice analyzing the case of two low-carbon communities (i.e.: before the XVI century, when the massive diffusion and use of coal modified these conditions) depends on the present international political will and plans of decarbonizing our societal lifestyles. This research highlights the hidden environmental causes behind the social instability and, in one case, the collapse of the community. Besides further reasons for historical interest, which are not deepened in this research, these case studies show that environmental factors are often unseen or neglected in planning the life of a community, also exerting a strong influence on real economy at local level. In order to develop appropriate policies to guarantee a long-term resilience for the socio-ecological stability of communities, an adequate monitoring of appropriate environmental and social parameters can sup-port planning activities.